Pengelolaan Taman Baca Masyarakat Ruang Membaca Aksara Di Kampung Cemplang Baru Kota Bogor - Atilla Tifanitrisma Yunia; Tika Santika; Abdul Muis (Jurnal Ilmiah Wahana Pendidikan, 2022)
The aims of this study are as follows: (1) To describe the planning of the Rumaksa reading garden program in the city of Bogor. (2) To describe the organization of the Rumaksa reading garden program in the city of Bogor. (3) To describe the organization of the Rumaksa reading garden program in the city of Bogor. (4) To describe the supervision of the Rumaksa reading garden program in the city of Bogor. The research method used in this study uses a qualitative approach with a descriptive method. The research subjects consisted of managers, volunteers, and 2 study residents. The research data were obtained through observation, interview, and documentation techniques. The results showed that (1) the planning of the Rumaksa community reading park was designed through an analysis of the needs of the local community (2) the organization of the Rumaksa community reading park program involved all volunteers who acted as educators. (3) the implementation of the Rumaksa community reading park program uses a diverse strategic approach (4) the supervision of the Rumaksa reading garden program is carried out in accordance with the ongoing learning activities.